Valuation of urban nature-based solutions in Latin American and European cities - Wild, Tom (2024)
The potential of urban nature-based solutions (NBS) to provide significant benefits to citizens and to address societal challenges is undervalued, yet the valuation of NBS impacts remains contentious. Further development of monetary and non-monetary valuation of the costs and benefits of urban NBS is required, and effective knowledge exchange on these themes is required at the international level. However, an important gap in research relates to the uptake and application of existing techniques for monetary valuation. This research explored how monetary values of urban NBS are assessed, and how NBS valuation is viewed by city government authorities in particular. Results are presented from a review of peer-reviewed articles reporting urban NBS valuation techniques development and application. Over 200 articles relating specifically to urban NBS interventions were reviewed. The literature indicates that many valuation techniques have been researched, but most studies tend to address just a few indicators of NBS impacts, which are mainly physical-environmental in their focus. To generate deeper insights into perceptions of monetary valuations in NBS impact assessments and their application, focus groups and semi-structured interviews were conducted with local and regional government staff in seven cities in Latin America and Europe. Although a wide range of economic valuation tools exist and can be applied to support NBS development, limited evidence was found for their uptake and application in practice across the contexts examined. We discuss potential reasons for limited uptake, which may include overburdensome data demands, incommensurability with existing decision-making and accounting practices, and limited staffing, financial and technical capacity - even within large cities. Results suggest that successful NBS interventions may portray economic impacts, but NBS propositions should not depend upon monetary valuations alone; social and ecological criteria remain centrally important. Participatory impact assessment methods may support improved business cases and monetary valuations for urban NBS.